2016
DOI: 10.1371/journal.ppat.1006060
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Mosquito Reproduction and Parasite Development for Malaria Control

Abstract: The control of mosquito populations with insecticide treated bed nets and indoor residual sprays remains the cornerstone of malaria reduction and elimination programs. In light of widespread insecticide resistance in mosquitoes, however, alternative strategies for reducing transmission by the mosquito vector are urgently needed, including the identification of safe compounds that affect vectorial capacity via mechanisms that differ from fast-acting insecticides. Here, we show that compounds targeting steroid h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 55 publications
5
79
0
Order By: Relevance
“…Following on from earlier laboratory studies that demonstrated that topical application of the 20E agonist methoxyfenozide caused sterility and a reduction in lifespan in female An. gambiae mosquitoes (Childs et al, 2016), we demonstrate that this chemistry has a similar effect on multiple insecticide resistant Anopheles populations. Crucially, we also show that, with the addition of the adjuvant RME, methoxyfenozide interrupts egg development through tarsal contact Furthermore, blood fed females had a significant reduction in life span post methoxyfenozide exposure.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Following on from earlier laboratory studies that demonstrated that topical application of the 20E agonist methoxyfenozide caused sterility and a reduction in lifespan in female An. gambiae mosquitoes (Childs et al, 2016), we demonstrate that this chemistry has a similar effect on multiple insecticide resistant Anopheles populations. Crucially, we also show that, with the addition of the adjuvant RME, methoxyfenozide interrupts egg development through tarsal contact Furthermore, blood fed females had a significant reduction in life span post methoxyfenozide exposure.…”
Section: Discussionmentioning
confidence: 57%
“…An 8% stock solution of the compound methoxyfenozide (MET) (Sigma-Aldrich) was prepared in DMSO; this stock was diluted in acetone to a 0.4% to match the concentration used in previous studies (Childs et al, 2016). Mosquitoes were anesthetized using carbon dioxide, placed on a petri dish lined with filter paper with the thorax exposed and held on a 4°C chill table (BioQuip products, Rancho Dominguez, CA).…”
Section: Topical Application or Methoxyfenozidementioning
confidence: 99%
See 2 more Smart Citations
“…http://dx.doi.org/10.1101/248112 doi: bioRxiv preprint first posted online Jan. 15, 2018; field use of 20E receptor agonists has been recently proposed to reduce malaria transmission (17). However, a limited number of Anopheles species have been studied.…”
mentioning
confidence: 99%